Assessment of Thyroid Disease Detection in Breast Pathologies - Zurabashvili, Marina; Kvanchakhadze, Rusudan (Caucasus Journal of Health Sciences and Public Health, 2020)
Despite the wide range of modern studies, the existence of appropriate methods of treatment and prophylaxis, malignant tumors of the breast and thyroid gland remain one of the most pressing problems in medicine. Severe clinical forms, complication and high mortality from these diseases are of great interest to practicing physician and scientists. Breast and thyroid cancer are the two most malignant diseases amongst women worldwide. Malignant growths of these orangs are often found simultaneously, and the causes of these concomitant diseases are still unknown. Women with thyroid cancer have a higher risk of developing breast cancer later on. The main causative factors of tumor formation are primary chemotherapy and radiation therapy, genetics, disfunction of thyroid hormones and estrogens, unhealthy lifestyle, bad habits, excess weight, environmental factors, etc